THE EFFECT OF THE USE OF GOOGLE CLASSROOM ON LEARNING INDEPENDENCE AND MATHEMATICS LEARNING OUTCOMES OF STUDENTS OF SMK NEGERI 3 KUPANG DURING PANDEMIC - Inda Adriyeni Murni Banunaek; Christine K. Ekowati; Damianus D. Samo (Academic Journal of Educational Sciences, 2022)
The rapid and massive spread of COVID-19 in the world, including Indonesia, has greatly affected various fields of life, including education. Therefore, in order for the learning process to continue during this pandemic, a strategy is needed to meet educational needs during the pandemic. The online learning process or online (on the network) uses an application that can support distance learning namely google classroom. This of course requires students to be active and critical independently in studying the topics studied in learning activities. The research was conducted at SMK Negeri 3 Kupang with a population of all students of class XI majoring in Computer and Network Engineering. Samples were taken as many as 60 students. From the results of the analysis, there is an effect of using google classroom on learning independence as shown in the results of the statistical test, the value of Fcount = 5.74 > Ftable = 2.76 and the value of Sig. 0.002 < 0.05 so that H0 is rejected. There is no significant effect of using google classroom on student mathematics learning outcomes, as shown in the results of the statistical test, the value of Fcount = 2.59 < Ftable = 2.76 and sig. 0.61 > 0.05 so that H0 is accepted. There is an effect of using google classroom on independent learning and student mathematics learning outcomes as shown by the results of MANOVA statistical analysis, it is known that the statistical value of the Pillai's Trace test is 0.618 and the value of Fcount = 8.341 > Ftable = 2.18 and the value of Sig. 0.000 < 0.05 so H0 is rejected. And there is an influence between learning independence on students' mathematics learning outcomes, as shown in the results of a simple linear regression statistical test, it is known that the value of ttable = 2.00172 > tcount = 22.138 so that H0 is rejected.